Personalizing instruction for children aged 5-6 in the acquisition of fundamental football skills - Antipov D.A. ,; Antipov A.V. ,; Tarasova L.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to validate and demonstrate the efficacy of personalized training for children aged 5-6 years in the development of fundamental football skills. Methods and structure of the study. The experiment was carried out from September 2021 to November 2023, involving 32 children aged 5-6 from FC Strogino and FC Lokomotiv (Moscow). The experiment involved individual lessons as an additional form of coaching for children already enrolled in the football schools of FC Strogino and FC Lokomotiv (Moscow). This approach allowed for a personalized impact on each student and the creation of a «school of movements» for future purposeful training in playing techniques. The effectiveness of this approach was evaluated by measuring the changes in technical preparedness indicators. Results and conclusions. The personalization of training sessions for young football players aged 5-6, which includes supplementary instruction, fosters the effective improvement of technical skills and the ability to apply them in game situations. Therefore, for children aged 5-6 who participate in football, it is essential to provide them with additional individualized training sessions, such as one-on-one coaching, which can help them catch up with their peers in a relatively short period of time. These sessions take into account the unique developmental characteristics of each child's body.